Role of epigenetics and DNA-damage in asthma. Issue 1 (February 2018) - Zahiruddin, Adil S.; Grant, J. Andrew; Sur, Sanjiv
Abstract : Purpose of review: Although asthma is a common disease worldwide, its pathogenesis remains to be fully elucidated. There is increasing evidence of the interaction between epigenetics, DNA-damage, and environmental allergens in the development of asthma. In this review, we will focus on the role of epigenetics and DNA-damage in asthma. Recent findings: There is growing evidence of environmental allergens, particularly house dust mite, stimulating oxidative DNA damage in airway epithelial cells. The repair of this DNA damage has been implicated in the secretion of Th2 cytokines and the induction of allergic inflammation. Summary: Studies of the role of epigenetics, DNA-damage, and environmental allergens have begun to reveal the their complex interactions and their roles in the development of asthma. Further study in these areas may lead to novel prevention and treatment approaches.